Adults' Motivation for Physical Activity: Differentiating Motives for Exercise, Sport, and Recreation. Issue 2 (October 2014) - Ball, James Warren; Bice, Matthew R.; Parry, Thomas
Physical inactivity continues to be a significant problem that adversely impacts adult health. An important construct to consider in researching adult physical activity adherence is motivation. Factors motivating participation in two types of physical activity, exercise and sport, have been compared; however, factors motivating participation in another type of physical activity, recreation, have often been left out of the comparison. The current study compared motivation to partake in physical activity among adults whose primary type of physical activity was exercise, sport, or recreation. Results indicate that participation motivation significantly varied among physical activity types (exercise, sport, and recreation). It was found that the participants who engaged in recreation as their primary form of physical activity and the participants who took part in exercise as their primary form of physical activity had motivations that were more similar to one another's than to those of the participants who use sport as their primary form of physical activity. Specifically, the findings suggest that participants who use exercise and recreation activities as their primary form of physical activity are motivated by more extrinsic constructs, compared to those who engage in sport as their primary form of physical activity. Findings provide insight that can be used to facilitate improved adherence to physical activity recommendations.